2016
DOI: 10.1039/c6nr03122f
|View full text |Cite
|
Sign up to set email alerts
|

High-responsivity graphene-on-silicon slot waveguide photodetectors

Abstract: We demonstrated strong optical absorption in a graphene integrated silicon slot waveguide. Due to the increase in light intensity and decrease of optical mode confinement in the silicon slot, the graphene experienced an increased interaction to the in-plane light. A waveguide absorption of 0.935 dB μm(-1) was measured at 1.55 μm wavelengths. Based on the graphene-on-silicon slot waveguide, a compact and high-responsivity photodetector was demonstrated. Benefited from the lack of efficient electron cooling in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 48 publications
4
114
2
Order By: Relevance
“…Here, we reviewed a subset of applications: optical interconnect technologies including high-speed photodetectors [15,16,39] and modulators [10,13], as well as device concepts for photonic quantum information processing, including progress toward efficient single photon sources and single photon detectors. With the exceptional progress of the past decade, such a scalable 2D nanophotonic architecture could bring remarkable impacts for these applications in the near future, while promising other directions including back-end deposited silicon photonics [118], mid-infrared photonics [119], THz detection [120,121] and modulation [122], and also flexible photonics [123].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we reviewed a subset of applications: optical interconnect technologies including high-speed photodetectors [15,16,39] and modulators [10,13], as well as device concepts for photonic quantum information processing, including progress toward efficient single photon sources and single photon detectors. With the exceptional progress of the past decade, such a scalable 2D nanophotonic architecture could bring remarkable impacts for these applications in the near future, while promising other directions including back-end deposited silicon photonics [118], mid-infrared photonics [119], THz detection [120,121] and modulation [122], and also flexible photonics [123].…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies to enhance the absorption include sandwiching the graphene layer inside a dielectric slot waveguide [38] or modifying the electric field distribution by creating an air slot in the middle of a channel waveguide. Wang et al achieved absorption as high as ~ 1 dB/μm by coupling graphene to such a silicon air-slot waveguide [39].…”
Section: Absorption Enhancement Of 2d Materials Integrated With Opticmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [54] demonstrated the high-responsivity graphene photodetector integrated on the silicon slot waveguide, as shown in the schematic of Figure 4(b). According to the simulation, among the four types of waveguides, namely, graphene-onsilicon TE/TM mode channel waveguides and graphene-onsilicon TE/TM slot waveguides, the graphene-on-TE mode waveguide showed the maximum optical absorption after optimization, as shown in Figure 4(b).…”
Section: Waveguide-integrated Graphene Photodetectorsmentioning
confidence: 99%
“…Many papers about graphene on photonic integrated circuits, especially about waveguide integrated graphene modulators and photodetectors have been published in the last few years [12][13][14]. The first graphene-based modulator was manufactured by Liu.…”
Section: Introductionmentioning
confidence: 99%